Body weight perception among Sri Lankan cardiac patients - Jayawardena, Ranil (BMC Obes, 2016)
BACKGROUND: Misperception of body weight by individuals is a known occurrence. However, it is a potential target for implementing obesity reduction interventions in patients with cardiovascular and metabolic diseases. The aim of this study was to describe the association between self-perception of body weight and objectively measured body mass index (BMI) among cardiac patients in a specialist cardiology institution in Sri Lanka. METHOD: During the study period, 322 (61 %) males and 204 (39 %) females were recruited from consecutive admissions to the Institute of Cardiology, National Hospital, Colombo, Sri Lanka. An interviewer-administered questionnaire was used to assess demographic characteristics, medical records and body weight perception. Weight, height and waist circumference (WC) were measured and Asian anthropometric cut-off points for BMI and WC were applied. RESULTS: The mean BMI of the study population was 23.61 kg/m(2). Body size misperception was seen in a significant proportion of the cohort. 85.2 % of overweight patients reported themselves to be of ‘normal weight’ or even ‘underweight’. Moreover, 36 % of obese patients misperceived body weight as being of ‘normal weight’ while 10.9 % considered themselves to be ‘underweight’. 61.9 % of males and 68.8 % of females with central obesity reported themselves to be ‘underweight’ or ‘normal weight’. Among a subgroup with co-morbid metabolic diseases, significant under-perception of body size was seen. CONCLUSIONS: Significant body size misperceptions were noted in this group of cardiac patients. The disparity of perception was seen increasingly with increasing BMI. More than two thirds of overweight and more than half of obese patients believed themselves to have normal or less than normal weight. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s40608-016-0113-5) contains supplementary material, which is available to authorized users.